Diagnostics and evaluation of biliary deposit at ultrasound investigation - Z. A. Lemeshko; M. A. Tatarkina; S. V. Nasonova; A. V. Okhlobystin (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
National college of gastroenterologists, hepatologists